Tantangan Pengembangan Ilmu di Era Digital Bagi Guru Sma: Sebuah Tinjauan Filsafat Ilmu - Mardiah, Suci Amelia; Karneli, Yeni; Handayani, Puji Gusri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The digital era has a major impact on how teachers approach, construct and apply science in educational contexts. This study aims to find challenges in developing science from the perspective of scientific philosophy, especially the essence, epistemology and axioms based on scientific articles. The results of the study indicate that teachers face fundamental changes in the validity of knowledge, obtaining information and moral responsibility in using it. On the other hand, administrative and systematic costs are practical obstacles in the development of teacher experts. Therefore, it is necessary to improve digital reading and writing skills, to improve the philosophical foundations of teaching activities, and to support political support for the sustainable development of science in secondary education environments.